Carp edema virus‐related mortality in wild adult common carp (cyprinus carpio) in Italy. Issue 7 (16th February 2021) - Marsella, Andrea; Pretto, Tobia; Abbadi, Miriam; Quartesan, Rosita; Cortinovis, Luana; Fiocchi, Eleonora; Manfrin, Amedeo; Toffan, Anna
Abstract: Mortality in wild fish populations represents a challenging issue for public fish health inspectors. When a single fish species is involved, an infective aetiology is frequently suspected, with focus on viral notifiable diseases. However, other viral agents not subjected to regulation and causing mortality in common carp have been reported such as carp edema virus (CEV). In mid‐June 2020, a severe common carp mortality was observed in an artificial lake in north‐east of Italy. Sleepy fish were noted some days before the beginning of the mortality itself, which lasted several days and involved over 340 adult specimens. During the outbreak, water temperature was around 15°C, water quality was normal, and no adverse meteorological events were reported in the area. Four specimens, which showed severe cutaneous hyperaemia and increased mucus production on skin and gills, were tested by bacteriological methods and virological analysis targeting the main carp pathogens. Molecular analysis performed on gills, kidney and brains from all the fish analysed resulted positive for CEV, which, based on anamnestic information and laboratory findings, was considered the responsible for the mortality event herein described.